Determination of persimmon leaf chloride contents using near-infrared spectroscopy (NIRS) - De-Paz, José M.; Visconti, Fernando; Chiaravalle, Mara; Quinones, Ana (Springer Verlag, 2020)
Early diagnosis of specific chloride toxicity in persimmon trees requires the reliable and fast determination of the leaf chloride content, which is usually performed by means of a cumbersome, expensive and time-consuming wet analysis. A methodology has been developed in this study as an alternative to determine chloride in persimmon leaves using near-infrared spectroscopy (NIRS) in combination with multivariate calibration techniques. Based on a training dataset of 134 samples, a predictive model was developed from their NIR spectral data. For modelling, the partial least squares regression (PLSR) method was used. The best model was obtained with the first derivative of the apparent absorbance and using just 10 latent components. In the subsequent external validation carried out with 35 external data this model reached r 2 = 0.93, RMSE = 0.16 % and RPD = 3.6, with standard error of 0.026 % and bias of −0.05 %. From these results, the model based on NIR spectral readings can be used for speeding up the laboratory determination of chloride in persimmon leaves with only a modest loss of precision. The intermolecular interaction between chloride ions and the peptide bonds in leaf proteins through hydrogen bonding, i.e. N–H···Cl, explains the ability for chloride determinations on the basis of NIR spectra.